The Role of Green Finance in Supporting Sustainable Natural Resource Management: An Institutional Perspective on OECD Countries Using an SLR - Alifia Salmaa Salsabila; Bhimo Rizky Samudro; Suryanto Suryanto (Jurnal Kewirausahaan dan Bisnis, 2026)
Green finance has emerged as an important policy instrument for supporting low-carbon development and sustainable natural resource management. This study synthesises the relationship between green finance, institutional quality, and environmental outcomes, with particular attention to OECD countries. A systematic literature review was conducted in accordance with the PRISMA 2020 framework. Following predefined inclusion and exclusion criteria, 59 peer-reviewed articles published between 2020 and 2026 were selected from Scopus, Web of Science, ScienceDirect, SpringerLink, Crossref, and Google Scholar. The studies were examined through descriptive, thematic, and bibliometric analyses to identify publication trends, dominant themes, institutional mechanisms, and research gaps. The evidence indicates that green bonds, sustainable banking, ESG-oriented finance, and renewable-energy financing can support emissions reduction, energy efficiency, clean-energy deployment, and sustainable economic development. However, these effects are conditional on regulatory quality, policy consistency, transparency, accountability, and implementation capacity. Evidence from OECD economies generally shows stronger integration between financial instruments and environmental policy, whereas studies of emerging economies more frequently identify market, institutional, and regulatory constraints. This review contributes by clarifying the institutional conditions under which green finance can support sustainable natural resource management and by identifying priorities for comparative research, meta-analysis, and the measurement of biodiversity, water, and ecosystem outcomes.Keywords: ESG finance; environmental governance; green finance; green bonds; institutional quality; renewable-energy financing